The use of antidepressants by children and adolescents: An integrative review (Research, Society and Development, 2024)
Depression, a chronic and recurrent psychiatric condition, is characterized by emotional fluctuations, including irritability, lack of motivation, changes in sleep and appetite, persistent feelings of sadness, distress, and guilt, as well as low self-esteem, associated with difficulty concentrating, suicidal thoughts, and indecision. The aim of this study was to describe the outcomes of pharmacotherapy used in the treatment of depression in children and adolescents. An integrative review was conducted in the MEDLINE and LILACS databases using the descriptors: Depressive Disorder, Antidepressive Agents, Child and Adolescent. Full-text articles published in the last five years, in English, Portuguese, or Spanish, addressing children and adolescents, were included. Repeated studies, reviews, dissertations or theses, or those that did not address pharmacological treatment outcomes were excluded. The final sample comprised eight articles. The effectiveness of pharmacotherapeutic interventions, such as the use of ketamine and fluvoxamine, in reducing depressive symptoms in children and adolescents, while also suggesting an association between levels of inflammatory cytokines and the severity of depressive symptoms, as well as highlighting the influence of personality traits on antidepressant treatment response. It is concluded that pharmacological interventions were associated with significant improvements in depressive symptoms, ranging from the use of intravenous ketamine, fluvoxamine, conventional antidepressants, and sertraline.